Postharvest UV-C Irradiation Influenced Cellular Structure, Jasmonic Acid Accumulation, and Resistance Against Green Mold Decay in Satsuma Mandarin Fruit (Citrus unshiu) - Phonyiam, Orathai; Ohara, Hitoshi; Kondo, Satoru; Naradisorn, Matchima; Setha, Sutthiwal (Frontiers in Sustainable Food Systems, 2021)
Green mold caused by Penicillium digitatum is an important factor limiting the shelf life of mandarin fruit. In this study, the effect of ultraviolet-C (UV-C) irradiation on cellular structure, endogenous jasmonic acid (JA) and development of P. digitatum in satsuma mandarin fruit were investigated. UV-C treatments included 0 (untreated control), 3 and 10 kJ m-2 or the exposure time of 0, 1.18, and 4.52 min, respectively. The UV-C dose of 10 kJ m-2 significantly reduced the development of P. digitatum both in vitro and in vivo, resulting in the maintenance of the cellular structure of the albedo tissue. The production of malondialdehyde (MDA) was decreased upon UV-C treatment of 10 kJ m-2. The concentration of JA increased in the treatment of 10 kJ m-2 compared to the treatment of 3 kJ m-2 and the control. UV-C irradiation increased total phenolic and total flavonoid concentrations and DPPH radical scavenging capacity. These results suggest that UV-C at 10 kJ m-2 has a potential to control green mold caused by P. digitatum, maintain cellular structure, stimulate the accumulation of JA, and induce of biochemical compounds in satsuma mandarin.